The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.3329/ajmbr.v1i2.25606
|View full text |Cite
|
Sign up to set email alerts
|

Serological response of commercial dairy cattle to inactivated foot-and-mouth disease vaccine (type-O & A) in Nigeria

Abstract: An observational study was conducted in a peri-urban dairy establishment in Jos South, Plateau State Nigeria to determine immune response of dairy cattle to commercial inactivated foot-and-mouth disease vaccine serotypes (O and A). Thirty seven Friesian cattle aged ?2years old with their crosses (15 selected pre-vaccination and 22 selected 21 days post-vaccination) were investigated for immune response to vaccination with an inactivated trivalent FMD vaccine containing serotypes O, A and SAT 2). Sera collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…This study has demonstrated that FMDV remains endemic among pastoral and sedentary husbandry systems within the study areas with multiple serotypes widely distributed. The four FMDV serotypes detected in the course of these studies along with previous reports in Nigeria establish the facts that these are the most prevalent serotypes circulating among cattle in the country [ 7 , 9 , 18 , 19 ]. However, to the best of our knowledge, this study has provided the first comprehensive spatial distribution of FMDV serotypes in the North-Central Nigeria, indicating only quadravalent vaccine, including the local isolates containing serotypes A, O, SAT 1, and SAT 2, should be used for vaccination campaign against FMD in Nigeria.…”
Section: Discussionsupporting
confidence: 76%
“…This study has demonstrated that FMDV remains endemic among pastoral and sedentary husbandry systems within the study areas with multiple serotypes widely distributed. The four FMDV serotypes detected in the course of these studies along with previous reports in Nigeria establish the facts that these are the most prevalent serotypes circulating among cattle in the country [ 7 , 9 , 18 , 19 ]. However, to the best of our knowledge, this study has provided the first comprehensive spatial distribution of FMDV serotypes in the North-Central Nigeria, indicating only quadravalent vaccine, including the local isolates containing serotypes A, O, SAT 1, and SAT 2, should be used for vaccination campaign against FMD in Nigeria.…”
Section: Discussionsupporting
confidence: 76%
“…FMD was previously eliminated in certain developed nations such as the USA, Canada, Australia, England, and Japan through vaccination or by combusting infected animals, however, its reemergence poses a severe danger to both domestic and wild wildlife in such countries (Foxell, 2003;Neumann, 2012). As a result, FMD is now regarded as the most dangerous epizootic threatening illness in the globe (Lazarus et al, 2015;Singh et al, 2019). Bangladesh, India, Burma, Nepal, Pakistan, Cambodia, Laos, Vietnam, and Thailand are still affected by FMDV serotypes O, A, and Asia 1, where serotype 'O' has been a prevalent serotype in Southeast Asia for many years, particularly in Bangladesh (Shahiduzzaman et al, 2016;Brito et al, 2017;Blacksell et al, 2019;Arju et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the annual FMD burden in Nigeria, seroepidemiology and serotyping studies for FMD infections are inadequate. e current trend of FMD occurrence in Nigeria showed that there are regular outbreaks, poor control measures, and lack of enforcement of legislation guiding disease reporting to veterinary authority [24,25]. e presence of antibodies to FMDV in several wildlife species has been documented in studies conducted in different countries of Africa mainly eastern and southern regions [26][27][28].…”
Section: Introductionmentioning
confidence: 99%